FROM INSIGHTS TO STRATEGY: MAPPING ROME’S CULTURAL HERITAGE FOR OPTIMAL RESOURCE MANAGEMENT AND PROMOTION - Masili, Giorgia; Conigliani, Caterina; Addis, Michela (Piccola Impresa / Small Business, 2025)
Purpose: This study analyses the distribution of Rome’s cultural heritage (CH) to support more effective urban marketing and city branding strategies, promoting an equitable allocation of resources and the enhancement of the entire territory. Methodology: The research employs a detailed mapping of CH using the QGIS software and cluster analysis to identify inequalities in the distribution of cultural sites across Rome’s urban zones (UZs). Findings: As noted in previous studies, Rome presents an uneven distribution of CH with a strong concentration in the historical centre and an almost total absence in peripheral neighbourhoods. Moreover, the cluster analysis identified seven groups of UZs with different levels of cultural offerings, allowing for tailored strategic recommendations for each group. Implications: Diversifying the cultural offering and strategically redistributing resources can enhance the attractiveness of peripheral areas, encourage investments, and improve residents’ quality of life. An inclusive city branding approach fosters a more balanced image of Rome, stimulating tourism and sustainable development. Originality of the Study: This study combines spatial analysis and clustering to provide data-driven strategic guidelines for urban marketing and cultural heritage management, contributing to a fairer and more sustainable vision of Rome’s urban development.